Piastowie i Rurykowice: polsko-ruskie stosunki polityczne od X do połowy XII wieku - Benyskiewicz, Krzysztof (1959- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The monograph is devoted to Polish-Ruthenian relations over the period of almost two centuries. It is an attempt to reconstruct the political relations between Poland and Kievan Rus` from the end of the 10th to the middle of the 12th century. The history of contacts between the Piasts and the Rurikids starts with the invasion of Vladimir the Great on the state of Mieszko I in 981. The first chapter of the book concerns the issue of Mieszko I`s relations with Vladimir. In the era of Bolesław the Brave`s reign, the scope of mutual relationships expanded. The second chapter of the paper is devoted to the issues of eastern politics of this ruler. The Brave intervened in Rus` three times. The Kievan expedition of 1018 took a particularly spectacular course. After the death of Bolesław I, Iaroslav the Wise took the initiative in neighbourly relations.
Keywords: Piastowie; Rurykowice; stosunki polityczne; The Piasts; the Rurikids; political relations; polityka międzynarodowa; Polska; Ruś